2018
DOI: 10.18433/jpps30010
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Gemini Surfactant-Based Lipoplexes Modified with Cell-Binding Peptide for Targeted Gene Therapy in Melanoma Model

Abstract: Purpose Achieving successful gene therapy requires delivery of a gene vector specifically to the targeted tissue with efficient expression and a good safety profile. The objective of this work was to develop, characterize and determine if a novel gemini surfactant-based lipoplex systems, modified with a cancer-targeting peptide p18-4, could serve this role. Methods The targeting peptide p18-4 was either chemically coupled to a gemini surfactant backbone or physically co-formulated with the lipoplexes. The infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…44 They proposed a correlation between nonlamellar lipid organization in lipoplexes with transfection efficiency. The correlation between a nonbilayer phase of the lipoplex and its high transfection activity is still being reported in literature, 45,46 but does not seem to be a general finding. For example, Tassler et al found that lysine-based amino-functionalized lipids, that varied in their chain length and (un)saturation, formed cubic or lamellar lipoplexes.…”
Section: Endosomal Escape Of Gene Delivery Devicesmentioning
confidence: 95%
“…44 They proposed a correlation between nonlamellar lipid organization in lipoplexes with transfection efficiency. The correlation between a nonbilayer phase of the lipoplex and its high transfection activity is still being reported in literature, 45,46 but does not seem to be a general finding. For example, Tassler et al found that lysine-based amino-functionalized lipids, that varied in their chain length and (un)saturation, formed cubic or lamellar lipoplexes.…”
Section: Endosomal Escape Of Gene Delivery Devicesmentioning
confidence: 95%
“…The obtained iDPP/LACTB nanocomplex had a high transfection efficiency over PEI25K and Lipo3000, which benefited from the specific binding of iRGD to the integrin receptors overexpressed on the surface of melanoma cells. 34,35 After intravenous administration, the iDPP/LACTB nanocomplex could efficiently target and transfect cancer cells, resulting in the effective cancer treatment.…”
mentioning
confidence: 99%
“…In an attempt to ensure the effectiveness and safety, a cancer-targeting peptide p18-4 was modified with the lipoplexes. The p18-4 in the lipoplexes system demonstrated high efficiency in human malignant melanoma (A375) cells (Mohammed-Saeid et al, 2018).…”
Section: Lipoplexesmentioning
confidence: 99%